Teaching Foreign Languages in Inclusive Education - Nazaralievna, Toshmurodova Mukhabbat; Qizi, Bekmuratova Shohsanam Muxtorbek (European Journal of Life Safety and Stability (2660-9630), 2022)
The issue of teaching foreign languages in higher education is today is becoming one of the most pressing issues of the day. At present, the level of development of students’ knowledge in the Republic, opportunities, features and special or general education. In order to implement education in the system, an inclusive education system is being implemented.